2019
DOI: 10.1002/ece3.5555
|View full text |Cite
|
Sign up to set email alerts
|

Collinearity in ecological niche modeling: Confusions and challenges

Abstract: Ecological niche models are widely used in ecology and biogeography. Maxent is one of the most frequently used niche modeling tools, and many studies have aimed to optimize its performance. However, scholars have conflicting views on the treatment of predictor collinearity in Maxent modeling. Despite this lack of consensus, quantitative examinations of the effects of collinearity on Maxent modeling, especially in model transfer scenarios, are lacking. To address this knowledge gap, here we quantify the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 281 publications
(197 citation statements)
references
References 83 publications
(134 reference statements)
2
185
1
9
Order By: Relevance
“…Collinearity between annual precipitation (bio12) and precipitation in the warmest and coldest quarters (bio18, bio19) also occurred. Because multicollinearity does not affect Maxent model performance, we refrained from excluding single highly correlated variables. Moreover, De Marco and Nóbrega even suggest that the Maxent fitting process takes advantage of existing collinearity in finding a best set of parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Collinearity between annual precipitation (bio12) and precipitation in the warmest and coldest quarters (bio18, bio19) also occurred. Because multicollinearity does not affect Maxent model performance, we refrained from excluding single highly correlated variables. Moreover, De Marco and Nóbrega even suggest that the Maxent fitting process takes advantage of existing collinearity in finding a best set of parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Transferring a model across space and/or time may lead to extrapolation if the projected environments are novel relative to training environments. Several studies have found that environmental novelty 48,94,95 (D6) and collinearity shift (D7; changes of collinearity structure of covariates 77,96 ) reduce predictive performance, and recommended quantifying the novelty of the projected environments and the collinearity shift between the calibrated and to include bug fixes or revised default settings. For instance, the default transformation method of Maxent raw output was changed from 'logistic' to 'cloglog' between versions 3.3 and 3.4 80 .…”
Section: 142 54mentioning
confidence: 99%
“…The information regarding environmental data necessary to reproduce studies is similar across biological research, such as in studies of relationships between species richness and environmental gradients 108 . The modelling algorithm details in the checklist are applicable to other studies that use statistical models, such projected environments 96,97 . Further, different algorithms use different strategies to extrapolate (clamping, truncation, extrapolation 94,98 ); for example, the default clamping function in Maxent uses the marginal values in the calibration area as the prediction for more extreme conditions in transfer areas 22 .…”
Section: Implications For Other Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collinearity between variables in the SDMs may lead to over-fitting phenomenon. However, Xiao Feng et al reports that the strategy of excluding highly correlated variables has little impact because Maxent accounts for redundant variables [30]. Besides, the nineteen environmental variables are regular bioclimatic variables, and the growth and distribution of Sphagnum plants are susceptible to precipitation and temperature.…”
Section: Environmental Parametersmentioning
confidence: 99%